Publisher correction: Real-time magnetic resonance imaging - guided coronary intervention in a porcine model - Heidt, Timo; Reiss, Simon; Krafft, Axel Joachim; Özen, Ali Caglar; Lottner, Thomas; Hehrlein, Christoph; Galmbacher, Roland; Kayser, Gian; Hilgendorf, Ingo; Stachon, Peter; Wolf, Dennis; Zirlik, Andreas; et al. (Scientific reports, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
Gesehen am 28.05.2020